2015
DOI: 10.1080/09500693.2015.1045957
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prior-knowledge and Online Learning Approaches on Students’ Inquiry and Argumentation Abilities

Abstract: This study investigated the effects of students' prior science knowledge and online learning approaches (social and individual) on their learning with regard to three topics: science concepts, inquiry, and argumentation. Two science teachers and 118 students from 4 eighthgrade science classes were invited to participate in this research. Students in each class were divided into three groups according to their level of prior science knowledge; they then took either our social-or individual-based online science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 70 publications
2
30
0
1
Order By: Relevance
“…Yang, Lin, She and Huang (2015, pp. 1572-1573 report using "a two-tier multiple-choice diagnostic instrument developed to measure the degree of students' conceptual understanding in science (Cronbach's α = 0.81…)" as a measure of prior knowledge across six diverse topics: "(1) the classification of substances, (2) fire prevention, (3) thermal convection, (4) chemical reaction rates, (5) sound waves and (6) mass conservation" (p.1571).…”
Section: Examples Of Alpha Cited In Measuring Cognitive Constructsmentioning
confidence: 99%
“…Yang, Lin, She and Huang (2015, pp. 1572-1573 report using "a two-tier multiple-choice diagnostic instrument developed to measure the degree of students' conceptual understanding in science (Cronbach's α = 0.81…)" as a measure of prior knowledge across six diverse topics: "(1) the classification of substances, (2) fire prevention, (3) thermal convection, (4) chemical reaction rates, (5) sound waves and (6) mass conservation" (p.1571).…”
Section: Examples Of Alpha Cited In Measuring Cognitive Constructsmentioning
confidence: 99%
“…Finally, many studies have demonstrated that inquiry-based instruction can improve students' learning and their attitudes toward science (Chen & She, 2015;Furtak et al, 2012;Rönnebeck et al, 2016), and other studies have further suggested that inquiry-based science teaching benefits overachievers (Kuo et al, 2012;Raes et al, 2014;Yang et al, 2015). In addition, some studies have reported that students' epistemic beliefs influence their cognitive processes of thinking, reasoning, or knowledge acquisition, and predict their achievement in science (Hofer, 2001;Mason et al, 2013).…”
Section: Implications and Suggestionsmentioning
confidence: 99%
“…A number of online learning programs were developed to support students' use of scientific languages in argumentation (Yang et al, ; Golanics & Nussbaum, ; Hasancebi & Gunel, ). The programs situate learners in collaborative, virtual, and explorative environment, enable them to explore relevant information from multiple resource and support them to make statements and reflections based on multiple views (Meluso et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The integration of multimedia and games into the design of online learning would make the learning more effective and educationally entertaining (Alessi & Trollip, ). It has been reported that well‐designed online science learning environments support the development of students' science‐related abilities, including science attitudes (Barab & Dede, ; Maxmen, ; Papastergiou, ), understanding of scientific knowledge (Meluso, Zheng, Spires, & Lester, ), and scientific argumentation (Yang, Lin, She, & Huang, ; Golanics & Nussbaum, ), allowing these abilities to be developed more effectively. The existing research regarding text reading comprehension indicates that individuals rely on contextualization cues to obtain meanings (Gumperz, ).…”
Section: Introductionmentioning
confidence: 99%